Specific Drug Formulation Additives: Revealing the Impact of Architecture and Block Length Ratio - SENGE, MATHIAS (My University, 2015)
Combining poly(ethylene glycol) (PEG) with sequence-defined peptides in PEG-peptide conjugates offers opportunities to realize next-generation drug formulation additives for overcoming undesired pharmacological profiles of difficult small molecule drugs. The tailored peptide segments provide sequence-specific, noncovalent drug binding, and the hydrophilic PEG block renders the complexes water soluble. On the basis of a peptide sequence known to bind the photosensitizer m-tetra(hydroxyphenyl)chlorin (m-THPC) for photodynamic cancer therapy, a set of different conjugate architectures is synthesized and studied. Variations in PEG block length and amplification of the peptidic binding domain of PEG-peptide conjugates are used to fine tune critical parameters for hosting m-THPC, such as drug payload capacities, aggregation sizes, and drug release and activation kinetics.
PUBLISHED
Keywords: Cancer